Dancers' Joint Strategies for Achieving Turnout in Low and High Friction Conditions - Duncan, R.; Wild, C.; Ng, Leo; Hendry, D.; Carter, S.; Hopper, L.; Campbell, Amity (2020)
BACKGROUND: Dancing with legs externally rotated (turnout) is a fundamental element of ballet technique. A reliance on floor friction to achieve turnout may contribute toward the high injury rate in dancers. Joint strategies used by dancers in high and low friction turnout conditions are not well understood. OBJECTIVES: To quantify the lower limb and lumbar spine joint strategies used by female pre-professional dancers to achieve turnout in low-friction (rotation discs) and high-friction (functional and forced) conditions. METHODS: Twenty-three pre-professional female dancers participated in the study. A 12-camera motion analysis system collected hip and knee external rotation (ER), ankle abduction, and lumbar extension angles in three turnout conditions and passive hip ER range of motion angles. Repeated measures ANOVA analysed the differences between joint angles, maximum turnout angle (foot relative to pelvis), and available hip ER. RESULTS: Dancers demonstrated lower knee ER (18.5±4.8°) and ankle abduction (6.0±7.7°) angles during low-friction turnout compared to higher friction conditions (p<0.05). Dancers utilised between 70-83% of available hip ER within all conditions. Low-friction turnout demonstrated greater hip ER contribution within maximum turnout (43%) compared to higher friction conditions. Dancers demonstrated greater lumbar extension angles in low-friction turnout compared to higher friction conditions (p<0.05). CONCLUSIONS: Further hip ER strength training is required to promote greater hip ER range within the position. Rotation discs may be a valuable training tool as dancers demonstrated greater hip ER utilisation with less knee ER and ankle abduction; however, this position did promote undesirable lumbar extension.